Molecular Targeted Therapy of Lung Cancer - Takiguchi, Yuichi (Springer Singapore : Imprint: Springer, 2017)
This book discusses the latest molecular targeted therapy of lung cancer including its evaluation and future directions. It clearly illustrates the initial dramatic effectiveness of molecular targeted therapy, recurrence of the disease, overcoming the wide variety of resistance mechanisms using new-generation molecular targeted agents and potential novel approaches. It also outlines the increasing necessity for new diagnostic technology and strategies for managing different adverse effects and novel methods for evaluating effectiveness and safety. Edited and authored by opinion leaders, Molecular Targeted Therapy of Lung Cancer provides a comprehensive overview of the disease and its treatments. It is a valuable resource for graduate students, post-doctoral fellows and faculty staff, as well as researchers involved in clinical and translational research on lung cancer, helping promote new ideas for further advances.